Waterborne diseases prevention: evaluation of inspection scoring system for water sites according to water microbiological tests during the Athens 2004 pre-Olympic and Olympic period. Issue 10 (13th September 2006) - Hadjichristodoulou, Christos; Mouchtouri, Varvara; Vousoureli, Anastasia; Konstantinidis, Athanasios; Petrikos, Philipos; Velonakis, Emmanuel; Boufa, Panagiota; Kremastinou, Jenny
Abstract : Study objectives: To evaluate the inspection grading system for water sites implemented during the Athens 2004 Olympic inspection programme. Design: The relation between the standardised inspections results of 716 water supply systems and 289 public swimming pools, and microbiological test results of 2358 samples collected during inspections was examined. Setting: Athens, Thessaloniki, Patra, Volos, and Iraklio, Greece. Inspections and sampling conducted during a two year period before the 2004 Olympics. Main results: Swimming pools unsatisfactory inspection grading results were significantly associated with positive water microbiological test results (relative risk = 2.5, p<0.05). One of the six violations of swimming pools and five of the seven violations of water supply systems designated as "critical" water safety hazards in the inspection reports were significantly associated with positive microbiological test results. The receiver operating characteristic analysis identified the unsatisfactory score designed in the swimming pools standardised inspection report, as the ideal score (−15), in adequately producing positive microbiological test results (sensitivity 13.2%, specificity 89%). Conclusions: This study shows the utility of standardised inspection grading systems in waterborne diseases prevention planning and implementation strategies of policy makers and regulators. Future water quality assessment should be based on the implementation of a robust standardised inspection system and reduce the need of microbiological tests.